Long-term consequences in Covid-19 and Non-Covid19 patients survivors of critical illness. A descriptive study - Damico, V.; Margosio, V.; Nattino, G.; Crimella, F. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Critically ill patients may develop health problems related to their illness, injury, mechanical ventilation or other treatments. Such problems cannot be totally prevented and can continue after the patient leaves the hospital. Aim. To explore the level of anxiety, depression, post-traumatic stress Intensive Care Unit and quality of life in Intensive Care Unit survivors. A comparison analysis between Covid-19 patients and Non-Covid-19 patients was conducted. Methods. A prospective observational study exploring psychological, emotional, and behavioral difficulties experienced in patients admitted to Intensive Care Unit was performed. The study was conducted in an Italian adult 8-bed Intensive Care Unit, from July 2020 to April 2021, and followed-up until 25th May 2022. Data were collected during Intensive Care Unit stay (data collection of demographic and clinical characteristics) and 6 and 12 months after Intensive Care Unit discharge (interviews). Results. A total of 143 patients participated in the study, of which 54 were admitted for Covid-19 (37.76%). Depression symptoms were observed more among Non-Covid-19 patients compared to Covid-19 patients at six months (p= .037) and 12 months (p< .001) after Intensive Care Unit discharge. The quality of life perceived by the Intensive Care Unit patients surveyed improved between 6 and 12 months after discharge (Eq-VAS mean=62.03, + 11.2 vs Eq-VAS mean=66.6, + 9.8) (p=.034). Six months after Intensive Care Unit discharge, the mean of the perception of quality of life, for Covid-19 patients was 63.91 (sd ± 9.30), greater than Non-Covid-19 patients of the same period, which was 60.18 (sd ± 8.63) (p= .038). Conclusions Within 1 year from the acute infection, most hospital survivors of Covid-19 had good physical and functional recovery over time with better outcomes than other Intensive Care Unit patients and had returned to their original work and life.